Serum Thyroid Hormone Antibodies Are Frequent in Patients with Polyglandular Autoimmune Syndrome Type 3, Particularly in Those Who Require Thyroxine Treatment - Vita, Roberto; Santaguida, Maria Giulia; Virili, Camilla; Segni, Maria; Galletti, Marina; Mandolfino, Mattia; Di Bari, Flavia; Centanni, Marco; Benvenga, Salvatore (Frontiers in Endocrinology, 2017)
Polyglandular autoimmune disease (PAS) type 3 consists of autoimmune thyroid disease coexisting with ≥1 nonthyroidal autoimmune disease other than Addison’s disease and hypoparathyroidism. We evaluated the prevalence and repertoire of thyroid hormones antibodies (THAb) in PAS-3 patients. Using a radioimmunoprecipation technique, we measured THAb (T3IgM, T3IgG, T4IgM, T4IgG) in 107 PAS-3 patients and 88 controls (patients with autoimmune thyroid disease without any nonthyroidal autoimmune disease). Based on the selective coexistence of autoimmune thyroid disease with one nonthyroidal autoimmune disease (chronic autoimmune gastritis, nonsegmental vitiligo or celiac disease) patients were divided into group 1 (chronic autoimmune gastritis positive, n=64), group 2 (nonsegmental vitiligo positive, n=24) or group 3 (celiac disease positive, n=15). At least one of the four THAb was detected in 45 PAS-3 patients (42.1%) and 28 controls (31.8%), with similar rates in the three PAS-3 groups. The rates of T3Ab, T4Ab and T3+T4Ab were similar in groups 1 and 2, while in group 3 T3Ab were undetected (P= 0.02). In PAS-3 patients the rate of levothyroxine treatment was greater in THAb positive patients compared with THAb negative patients (76.7% vs. 56.1%, P= 0.03, RR= 1.4, 95%CI 1.03-1.81). Not unexpectedly, levothyroxine daily dose was significantly higher in group 1 and group 3, namely in patients with gastrointestinal disorders, compared with group 2 (1.9±0.4 and 1.8±0.3 vs. 1.5±0.2 μg/kg body weight, P= 0.0005 and P= 0.004). Almost half of PAS-3 patients have THAb, whose repertoire is similar if chronic autoimmune gastritis or celiac disease is present. A prospective study would confirm whether THAb positivity predicts greater likelihood of requiring levothyroxine treatment.